The Distribution of Corporate Ownership in the United States - Warshow, H. T. (Quarterly Journal of Economics, 1924)
An important movement, in need of quantitative measurement, 16. — Federal income-tax returns indicate a wider distribution of dividend payments, 17. — Corroborative evidence furnished by a study of stock ownership in 281 corporations, 21. — An estimate of total capital stock of American corporations and of the number of domestic stockholders, 26. — Two periods of rapid diffusion, 29. — Stock ownership by employees, 32. — By customers, 32. — Labor banks, 33. — Tax-exempt securities, 35. — Effect of Liberty Bond campaigns, 35. — Increase of savings deposits, 36. — Effect of higher wages, 37. — Conclusion, 38.